Analysis of recreational drug samples obtained from patients presenting to a busy inner-city emergency department: a pilot study adding to knowledge on local recreational drug use. Issue 1 (15th August 2010) - Wood, David M; Panayi, Panayiota; Davies, Susannah; Huggett, Denise; Collignon, Ursula; Ramsey, John; Button, Jenny; Holt, David W; Dargan, Paul I
Abstract : Introduction: Routine toxicological screening is not undertaken in individuals presenting to emergency departments (ED) with acute recreational drug toxicity, because it does not usually alter an individual patient's management. Localised information on the types of recreational drugs being used is often not available. The pilot study described here looks at the analysis of presumed recreational drugs in the possession of individuals presenting to the ED with acute recreational drug toxicity. Methods: Suspected recreational drug samples were handled as controlled drugs and transported to a Home Office approved laboratory. Samples were initially categorised on the basis of their physical appearance; liquid samples were analysed by infrared spectrophotometry and non-liquid samples were analysed by gas chromatography–mass spectrometry. Results: A total of 33 (12 liquid and 21 non-liquid) samples was analysed in this pilot study. Liquid samples were shown to contain either γ-butyrolactone or isopropyl nitrite. 19% of non-liquid samples (12% of total samples) did not contain any drugs and 23% contained legal pharmaceutical agents. Of the remaining samples, they contained both 'classic' and 'novel' recreational drugs. Only 33.3% of crystalline substances contained methamphetamine. Discussion: This pilot study has shown that analysing samples obtained in the ED can contribute to clinicians' knowledge of local drug epidemiology. Extension of this approach in areas with a high prevalence of recreational drug use, with appropriate funding, may be useful in monitoring drug trends and detecting novel emerging drugs.